1971
DOI: 10.1901/jeab.1971.15-193
|View full text |Cite
|
Sign up to set email alerts
|

ELICITATION AND PUNISHMENT OF INTRASPECIES AGGRESSION BY THE SAME STIMULUS1

Abstract: Fighting responses were elicited in pairs of rats by shocks over a period of 46 days. During certain blocks of these days, "punishing" shocks were made contingent on the shock-elicited fights. Fighting frequency was reduced as a direct function of the intensity of the contingent shocks. Fighting frequency recovered completely when contingent shocks were removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

1972
1972
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
3
11
1
Order By: Relevance
“…The results of these experiments corroborate the findings of Roberts and Blase (1971), that a stimulus of the same intensity and duration used to induce aggression can function to suppress aggressive behavior when that stimulus is presented contingent on the occurrence of that aggressive response. The results also indicated that the response-contingent shock punishment functioned to suppress shock-induced attack regardless of fighting history.…”
Section: G E N E R a L D Iscuss 1 0 Nsupporting
confidence: 85%
See 3 more Smart Citations
“…The results of these experiments corroborate the findings of Roberts and Blase (1971), that a stimulus of the same intensity and duration used to induce aggression can function to suppress aggressive behavior when that stimulus is presented contingent on the occurrence of that aggressive response. The results also indicated that the response-contingent shock punishment functioned to suppress shock-induced attack regardless of fighting history.…”
Section: G E N E R a L D Iscuss 1 0 Nsupporting
confidence: 85%
“…Consistent with the informal observations of Roberts and Blase (1971), the data of Experiment 2 showed that the punishment groups evidenced a longer duration of fighting per shock than the control groups, regardless of fighting history conditions. Because the duration group of Experiment 2 also showed this increased duration of attack, and because punishment most frequently increased shock duration, the increased duration of attack during punishment appears to be nothing more than a consequence of the increased shock duration during an attack-inducing trial.…”
Section: G E N E R a L D Iscuss 1 0 Nsupporting
confidence: 82%
See 2 more Smart Citations
“…Both Azrin (1970) and Roberts and Blase (1971) also used shock to punish shock-induced attack, in monkeys and rats, respectively, and found that attacks decreased as a function of the intensity of contingent shock. Other studies have involved artificially induced defeat following aggressive encounters (e.g., in mice: Hudgens and MacNeil, 1970;Kahn, 1951;Lagerspetz, 1964), with the result that attack became markedly reduced or absent on subsequent occasions.…”
Section: Introductionmentioning
confidence: 99%